Rekomendasi Adaptasi dan Mitigasi Bencana Banjir di Kawasan Rawan Bencana (KRB) Banjir Kota Bima - Rizki Kirana Yuniartanti (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Flood disaster occurred on December 21, 2016, December 23, 2016, and January 2, 2017 in Bima city area, covering Mpunda district, Rasanae Timur district, Asakota district, Rasanae Barat district, and Raba district. The urban area is the most affected area of flash flood, mainly residential areas that are located more than 50 meters from the flood plains, with flood heights ranging from 1 to 4 meters. The main factor that caused flood disaster is high rainfall. In addition to the hydrometeorological factor, flood in Bima city was caused by various factors, including its location at a basin area, flood plains that are utilized for settlements nowadays, silting downstreams, poor management of drainage systems, reduced vegetation-cover in the upstream, and narrowing of river bodies. Looking at the problems and challenges of the hydrometeorological disaster, this research aims to recommend adaptation and mitigation for flood disaster and space utilization conversion in disaster prone areas of Bima city. Analytical methods used in this research includes participatory mapping to delineate the flood affected area, HEC-RAS and HEC-GEORAS to map and model flood hazards, and quantitative descriptive to describe data and information. Output of this research are adaptation and mitigation recommendations based on the mapping of flood hazard areas and the modeling of flood disaster prone areas.